Emerging biomarkers of postoperative delirium at the intersection of neuroinflammation and neurodegeneration - Leng, Kun; Maze, Mervyn; Barreto Chang, Odmara L. (Frontiers in Aging Neuroscience, 2025)
Postoperative delirium (POD) is a common and severe neuropsychiatric complication affecting older adults after surgery. POD is characterized by fluctuating cognitive disturbances, impaired attention, and altered consciousness, resulting in increased morbidity and mortality, prolonged hospital stays, and higher healthcare costs. Systemic inflammation induced by surgical trauma is implicated in the pathophysiology of POD, although the subsequent mechanisms that produce blood–brain barrier (BBB) dysfunction, neuroinflammation, and interactions with underlying dementia neuropathology have not been resolved. Recent advances in biomarker research have shed light on predictive and diagnostic tools for POD. Biomarkers linked to dementia neuropathology (e.g., hyperphosphorylated tau, amyloid beta), neuronal injury (e.g., total tau, neurofilament light chain), glial activation (e.g., glial fibrillary acidic protein), and systemic inflammation (e.g., interleukin-6) have shown promise. The feasibility of measuring the above biomarkers in easy-to-obtain biofluids such as blood is enhanced by technologies like single-molecule array immunoassays, enabling sensitive detection of central nervous system markers at femtomolar concentrations. Emerging evidence highlights associations between POD risk and these biomarkers, although findings often vary due to cohort heterogeneity and methodological differences. This review critically examines the existing literature on POD biomarkers, focusing on their relevance to dementia neuropathology, neuronal injury, neuroinflammation, and BBB integrity. While significant strides have been made, gaps in knowledge persist, emphasizing the need for larger, more standardized studies. Developing robust biomarkers could transform POD prediction, diagnosis, and management, ultimately improving outcomes for vulnerable surgical populations.